Establishment of reference sequences of hepatitis B virus genotype B subgenotypes - Jin, Xiaojun; Cai, Qun; Zhang, Zhenhua; Sheng, Jifang (Archives of Biological Sciences, 2020)
Paper description: Some reference sequences of hepatitis B virus genotype B (HBV/B) are not sufficient to represent the reference of individual sub-genotypes. It is necessary to establish new reference sequences of the HBV/B sub-genotype. Genomic sequences of HBV/B were obtained from GenBank and compartmentalized into genomic subtypes. Homology between established HBV/B references was evaluated at the nucleotide level. Reference strains for B1-Japan, B2-China, B3-Indonesia, B4-Vietnam, B6-North America, B7-Indonesia and B9-Southeast Asia were established. Fractional significant mutation sites of strains were observed in the BCP/Pre-C regions. Reference sequences provide reference standards for molecular characterization, virology and pathogenesis of HBV/B. Abstract: Hepatitis B virus (HBV) has been classified into ten genotypes (A-J). Genotype B (HBV/B) is divided into nine subgenotypes (B1-B9), each with specific geographical predominance. Some reference sequence of HBV/B subgenotypes are currently in use, but these sequences have defects, being insufficient to represent the reference of individual subgenotype. The aim of this study was to establish a more representative reference of HBV/B subgenotypes in different regions. Full genomic sequences of HBV/B were obtained from GenBank and compartmentalized into genomic subtypes. The homology between our established HBV/B subgenotype references was evaluated at the nucleotide level. We established reference strains for B1-Japan, B2-China, B3-Indonesia, B4-Vietnam, B6-North America, B7-Indonesia and B9-Southeast Asia. Fractional significant mutation sites of the strains that were established were observed in the BCP/Pre-C regions. We calculated the genetic divergence time from the most recent common ancestor of HBV/B pedigree. The reference sequences established in the study provide reference standards for studies on molecular characterization, virology and pathogenesis of HBV/B.